Hubungan Antara Penggunaan Obat Kontrasepsi Oral Terhadap Penyakit Kanker Leher Rahim di RSPAD Gatot Soebroto Periode 2017-2018 - Verrichi Siregar; Hadi Nugroho; Okpri Meila (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
Cervical cancer is a primary malignant tumor originating from cervical squamous epithelial cells, the cause of cervical cancer is infection with the HPV virus (Human Papilloma Virus). Several factors are thought to increase the incidence of cervical cancer, namely age, occupation, exposure to hazardous substances, oral contraceptives, long-term use of oral contraceptives, smoking, and diet. The purpose of this study was to see whether there was a significant relationship between the use of oral contraceptives and the incidence of cervical cancer. The type of research used was a case control study, namely women with cervical cancer at Gatot Soebroto Army Hospital, and controls were women without cervical cancer at Gatot Soebroto Army Hospital. The results of this study indicate that there is a significant relationship between the use of oral contraceptives in the incidence of cervical cancer (p = 0.026), and there is a significant relationship between the use of long-term oral contraception against cervical cancer incidence (p = 0.004). In this study, the results of age, occupation, and smoking are risk factors for cervical cancer (OR> 1), and the results of this study show that exposure to hazardous substances and diet is not a risk factor for cervical cancer.